2021
DOI: 10.1017/s0007114521000490
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin induces mitochondrial biogenesis by increasing cyclic AMP levels via phosphodiesterase 4A inhibition in skeletal muscle

Abstract: Background: Previous research has suggested that curcumin potentially induces mitochondrial biogenesis in skeletal muscle via increasing cAMP levels. However, the regulatory mechanisms for this phenomenon remain unknown. The purpose of the present study was to clarify the mechanism by which curcumin activates cAMP-related signalling pathways that upregulate mitochondrial biogenesis and respiration in skeletal muscle. Methods: The effect of curcumin treatment (i.p., 100 mg/kg-BW/day for 28 days) on mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 45 publications
(57 reference statements)
0
7
1
Order By: Relevance
“…Acute exercise stimulates the PGC-1α in rodents and humans, and it helps to modulate muscle autophagy [ 27 ]. Although the previous studies reported that curcumin supplementation increased the PGC-1α protein levels or deacetylation in muscle tissue [ 13 , 28 , 29 ], we found that NGUC supplementation suppresses the muscle PGC-1α levels after one-time exhaustive exercise. Kang, et al [ 30 ] reported that attenuating the ROS releasing with allopurinol, an antioxidant, decreased the muscle PGC-1α levels following acute exercise.…”
Section: Discussioncontrasting
confidence: 87%
“…Acute exercise stimulates the PGC-1α in rodents and humans, and it helps to modulate muscle autophagy [ 27 ]. Although the previous studies reported that curcumin supplementation increased the PGC-1α protein levels or deacetylation in muscle tissue [ 13 , 28 , 29 ], we found that NGUC supplementation suppresses the muscle PGC-1α levels after one-time exhaustive exercise. Kang, et al [ 30 ] reported that attenuating the ROS releasing with allopurinol, an antioxidant, decreased the muscle PGC-1α levels following acute exercise.…”
Section: Discussioncontrasting
confidence: 87%
“…As a result, mitochondrial biogenesis and function are improved, which in turn protects against diet-induced obesity and glucose intolerance in mice. In line with these findings, Hamidie et al [ 74 ] have recently shown that intraperitoneal curcumin treatment in rats increased cAMP levels in muscle due to the inhibition of PDE4A. As a consequence, activation of the PKA-LKB1 axis followed by phosphorylation of AMPK and deacetylation of PGC-1α leads to the induction of mitochondrial biogenesis in skeletal muscle.…”
Section: Functional and Translational Significance Of The Camp/ampk Axismentioning
confidence: 72%
“…Rakshit et al [44] Hou et al [55] Yang et al [66] Sudeep et al [77] Lukitasari et al [88] Santana-Galvez et al [94] Cha et al [95] Wang et al [96] Santana-Galvez et al [94] Zeng et al [21] Chen et al [34] Zatorski et al [35] CUR Nakamae et al [36] Gupta et al [37] Gersey et al [38] Yu et al [39] Hamidie et al [40] Pan et al [41] Abadi et al [42] Park et al [43] Wang et al [45] Pimentel-Gutierrez et al […”
Section: Cgamentioning
confidence: 99%